2016
DOI: 10.1038/eye.2016.288
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine intake is associated with pupil dilation and enhanced accommodation

Abstract: PurposeIt is purported that caffeine, an autonomic stimulant, affects visual performance. This study sought to assess whether caffeine intake was associated with changes in pupil size and/or amplitude of accommodation.Patients and methodsA double-masked, crossover study was conducted in 50 healthy subjects of age range 19 to 25 years. Subjects were randomized to treatments such that subjects consumed either 250 mg caffeine drink or vehicle on separate days. Amplitude of accommodation was measured by the push-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…Unfortunately, we did not notice whether the participants had consumed caffeine prior to pupillometry. This could potentially affect the pupillometry outcomes, since caffeine has been associated with pupil dilation and increased accommodation (Abokyi et al 2017) In conclusion, this is the first study to investigate the function of ipRGCs and sleep quality in patients with NTG. We found that the melanopsin-mediated PLR was significantly reduced in patients with NTG, indicating impaired ipRGC activity.…”
Section: Discussionmentioning
confidence: 88%
“…Unfortunately, we did not notice whether the participants had consumed caffeine prior to pupillometry. This could potentially affect the pupillometry outcomes, since caffeine has been associated with pupil dilation and increased accommodation (Abokyi et al 2017) In conclusion, this is the first study to investigate the function of ipRGCs and sleep quality in patients with NTG. We found that the melanopsin-mediated PLR was significantly reduced in patients with NTG, indicating impaired ipRGC activity.…”
Section: Discussionmentioning
confidence: 88%
“…All reported having normal or corrected-to-normal vision and hearing and having no diagnosed neurological disease. No participants reported having used psychoactive substances up to 12 hours pre-experiment, as well as having consumed coffee, tea, or tobacco products up to 6 hours before the experiment as this could impact the baseline pupil diameter (Abokyi, Owusu-Mensah, & Osei, 2017;Lie & Domino, 1999).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Pupil dilations are larger after ingestion of caffeine ( Abokyi, Oqusu-Mensah, & Osei, 2017 ). Caffeine has been shown to affect the pupil response for up to about 6 h, particularly in people who do not routinely consume it ( Wilhelm, Stuiber, Lüdtke, & Wilhelm, 2014 ).…”
Section: Data Collectionmentioning
confidence: 99%